Hemoglobin Variant (Hemoglobin Aalborg) Mimicking Interstitial Pulmonary Disease - Vasiliki Panou; Peter-Diedrich Mathias Jensen; Jan Freddy Pedersen; Lars Pilegaard Thomsen; Ulla Møller Weinreich (Pulmonary Medicine)
Hemoglobin Aalborg is a moderately unstable hemoglobin variant with no affiliation to serious hematological abnormality or major clinical symptoms under normal circumstances. Our index person was a healthy woman of 58, not previously diagnosed with hemoglobinopathy Aalborg, who developed acute respiratory failure after a routine cholecystectomy. Initially she was suspected of idiopathic interstitial lung disease, yet a series of tests uncovered various abnormal physiological parameters and set the diagnosis of hemoglobinopathy Aalborg. This led us to examine a group of the index person’s relatives known with hemoglobinopathy Aalborg in order to study whether the same physiological abnormalities would be reencountered. They were all subjected to spirometry and body plethysmography, six-minute walking test, pulse oximetry, and arterial blood gas samples before and after the walking test. The entire study population presented the same physiological anomalies: reduction in diffusion capacity, and abnormalities in PaO2 and p50 values; the latter could not be presented by the arterial blood gas analyzer; furthermore there was concordance between pulse oximetry and arterial blood gas samples regarding saturation. These data suggest that, based upon the above mentioned anomalies in physiological parameters, the diagnosis of hemoglobinopathy Aalborg should be considered.